2006
DOI: 10.1590/s0102-86502006001000017
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative administration of probiotics: effects on immune response, anastomotic resistance and colonic mucosal trophism

Abstract: Purpose:To investigate the effects of perioperative administration of diet containing probiotics on the immune response, anastomotic resistance, and colonic mucosal trophism in rats underwent left-sided colonic anastomosis. Methods: Sixty adults Wistar rats were randomized to two groups (A and B) with 30 animals each to receive or not a diet supplemented with probiotics (Streptococcus thermophilus e Lactobacillus helveticus) during pre-and postoperative period. They underwent laparotomy followed by left colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In another study, the administration of an aproteic diet with L. helveticus Bionan (Nestlé, Brazil) in combination with S. thermophilus protected the colonic mucosa of mice by counteracting the effect of malnutrition and restoring the number of goblet cells (Dock-Nascimento et al, 2007). Analogously, the same probiotic preparation administered to mice in pre- and post-operative periods stimulated the immune system, increased the production of serum IgA and increased colonic weight (Aguilar-Nascimento et al, 2006). …”
Section: Other Proposed Health-promoting Properties Of L Helveticusmentioning
confidence: 99%
“…In another study, the administration of an aproteic diet with L. helveticus Bionan (Nestlé, Brazil) in combination with S. thermophilus protected the colonic mucosa of mice by counteracting the effect of malnutrition and restoring the number of goblet cells (Dock-Nascimento et al, 2007). Analogously, the same probiotic preparation administered to mice in pre- and post-operative periods stimulated the immune system, increased the production of serum IgA and increased colonic weight (Aguilar-Nascimento et al, 2006). …”
Section: Other Proposed Health-promoting Properties Of L Helveticusmentioning
confidence: 99%
“…Significant differences were observed with respect to the doses of probiotics used. However, no differences in results were noted between the highest (Beaulieu et al 2007) and lowest administered doses (Aguilar-Nascimento et al 2006): both showed positive immune responses. The immune response to the use of probiotics was also not dependent on the time of administration: positive responses were noted when probiotics were administered before pathogen challenge, during the challenge, or both before and after the challenge.…”
Section: Discussionmentioning
confidence: 79%
“…However, no trend was found among the studies analyzed regarding the type of microorganism used for the treatment, preventing the establishment of a general protocol. Lactobacillus were used against several different types of pathogenic challenges, including encephalomyelitis (Baken et al 2006;Maassen and Claassen 2008); colitis (Amit-Romach et al 2010); laparotomy with colon anastomosis (Aguilar-Nascimento et al 2006); and E. coli infection (Ishida-Fujii et al 2007), among others. With the exception of Baken et al (2006), all of these articles reported satisfactory results associated with the probiotic administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aguilar-nascimento et al showed that a diet supplemented with probiotics (Streptococcus thermophilus e Lactobacillus helveticus) during the pre-and postoperative periods in rats submitted to colonic resection and anastomosis enhanced colonic weight and anastomotic bursting strength postoperatively. IgA levels increased from intra-to postoperative periods only in animals receiving probiotics supplementation [22].…”
Section: Animal Studiesmentioning
confidence: 93%